Is microfinance better compared to other financial institutions? Analyzing the impact of various financial ac-cess on household welfare in Indonesia - Noer Fajrieansyah; Andy Fefta Wijaya; Imam Hanafia; Wike Wike; Farida Nurani; Fadillah Amin; Muhammad Saif (Decision Science Letters)
This study examines how access to different types of financial services influences household welfare in Indonesia. Using data from a large sample of 331,068 households, the research applies Ordinary Least Squares (OLS) regression to evaluate the impact of financial institutions on household income, which serves as a proxy for welfare. The findings reveal that access to microfinance and commercial banks significantly improves household income, highlighting the critical role these institutions play in enhancing welfare. Conversely, households relying on informal financial institutions tend to have lower incomes, indicating a negative effect on welfare. Further analysis reveals important variations based on gender and geographic location. Microfinance and cooperatives are particularly beneficial for female-headed households and those in rural areas, underscoring their importance in supporting underserved populations. On the other hand, access to commercial banks benefits both male and female headed households but has a stronger impact in urban areas where formal banking services are more readily available. While informal financial institutions negatively affect urban households, they provide modest advantages for female-headed and rural households, serving as an alternative in areas lacking formal financial services. These findings underscore the need for targeted financial inclusion policies that address gender and regional disparities. Such policies should prioritize expanding access to microfinance and cooperatives for rural and female-headed households while also improving access to formal banking services in urban areas to enhance overall welfare.